سرکاری عہدوں اور وسائل کا صحیح استعمال سیرت النبی کی روشنی میں : Responsible use of Government Positions and Resources in the light of the Prophetic teaching - Dr. Kafaitullah Hamdani; Dr. Mushtaq Ahmed (Al Manhal Research Journal, 2022)
Management is essential for the better functioning of human society. Because the solution to the problems of human society lies in the equitable distribution of available resources. To meet this need, responsible and eligible individuals of the society are assigned key posts and hard tasks. Naturally, when a person has acquired power and authority, his examination begins at that very moment. If he does not get proper guidance in the relevant field, he may be betraying and misuse his authorities. The Prophet (PBUH) is the only being, who guides humanity at every sphere of life . He is a perfect, complete, beautiful and ideal human being. He has left a perfect example for everyone in life. This paper deals with the great and exemplary teachings of the Holy prophet for all mankind.